Ecofriendly Printed Wood-Based Honey-Gated Transistors for Artificial Synapse Emulation - Vieira, Douglas Henrique (2024)
Funding Information: The authors acknowledge Fundação de Amparo à Pesquisa do Estado deSão Paulo (FAPESP, grants 2023/06645-5, 2022/16125-6, 2022/12332-7,2023/14843-1), Coordenação de Aperfeiçoamento de Pessoal de NívelSuperior (CAPES) - Finance Code 001, and Conselho Nacional deDesenvolvimento Cientíﬁco e Tecnológico (CNPq) for the ﬁnancial sup-port. The authors also acknowledge Programa de Pós-Graduação emCiência e Tecnologia de Materiais (POSMAT), Instituto Nacional deEletrônica Orgânica (INEO) for technical support. The authors acknowledge the SUPERIOT project whichhad received funding from the Smart Networks and Services JointUndertaking (SNS JU) under the European Union’s Horizon Europeresearch and innovation programme under grant agreement no 101096021, including funding under the UK government’s HorizonEurope funding guarantee. This work also received funding from the HORIZON-EIC-2023-PATHFINDERCHALLENGES-01 program [grant agreement no.101161114 (ELEGANCE)] Publisher Copyright: © 2024 The Author(s). Advanced Intelligent Systems published by Wiley-VCH GmbH.